Therapy-Induced Neuroplasticity in Chronic Aphasia After Phonological Component Analysis: A Matter of Intensity - Marcotte, Karine; Laird, Laura; Bitan, Tali; Meltzer, Jed A.; Graham, Simon J.; Leonard, Carol; Rochon, Elizabeth (Frontiers in Neurology, 2018)
Despite the growing evidence regarding the importance of intensity and dose in aphasia therapy, few well-controlled studies contrasting the effects of intensive and non-intensive treatment have been conducted to date. Phonological components analysis (PCA) treatment for anomia has been associated with improvements in some patients with chronic aphasia, however the effect of treatment intensity has not yet been studied with PCA. Thus, the aim of the present study was to identify the effect of intensity on neural processing associated with word retrieval abilities after PCA treatment. We used functional magnetic resonance imaging to examine therapy induced changes in activation during an overt naming task in two patients who suffered from a stroke in the left middle cerebral artery territory. P1 received intensive PCA treatment whereas P2 received the standard, non-intensive, PCA treatment. Behavioral results indicate that both standard and intensive conditions yielded improved naming performance with treated nouns, but the changes were only significant for the patient who received the intensive treatment. The improvements were found to be long-lasting as both patients maintained improved naming at 2-months follow-ups. The associated neuroimaging data indicate that the two treatment conditions were associated with different neural activation changes. The patient who received the standard PCA showed significant increase in activation with treatment in the right anterior cingulate, as well as extensive areas in bilateral posterior and lateral cortices. In contrast, the patient who received intensive PCA showed more decreases in activation following the treatment. Unexpectedly, this patient showed subcortical increase in activation, specifically in the right caudate nucleus. We speculate that the recruitment of the caudate nucleus and the anterior cingulate in these patients reflects the need to suppress errors in order to improve naming. Thus, both short-term intensive and standard, non-intensive, PCA treatment can improve word retrieval in chronic aphasia, but neuroimaging data suggest that improved naming is associated with different neural activation patterns in the two treatment conditions.